Lymphangioleiomyomatosis in patients with tuberous sclerosis: a national centre audit - Jan Johnson; Wendy Somerfield; Simon R. Johnson (Orphanet Journal of Rare Diseases, 2024)
Abstract Background Lymphangioleiomyomatosis (LAM) is common in tuberous sclerosis complex (TSC) yet under recognised with management mostly based upon evidence obtained from patients with sporadic LAM. We performed a prospective audit of patients with TSC-LAM attending a national referral centre to inform management guidelines. Methods The UK LAM Centre was established in 2011 and conducts a prospective audit of pre-defined quality outcomes for all subjects. Audit data are reported on all patients with TSC-LAM and a comparator population of patients with sporadic LAM. Results Between 2011 and 2022, 73 patients were seen with TSC-LAM. All were women with a mean (SD) age of 39 (12) years. Referral rates were similar over the study period including after the introduction of CT screening. Median age of diagnosis with TSC was 11 years (range 0–70) with one third diagnosed with TSC as adults. Compared with all TSC patients in the ‘TOSCA’ registry, TSC-LAM patients tended to have been diagnosed with TSC at an older age, had fewer neuro-cognitive manifestations and were more likely to have angiomyolipoma. The most common presentations of TSC-LAM were following workup for angiomyolipoma, pneumothorax or dyspnoea with only one fifth detected after CT screening. Baseline FEV1 and DLCO at first assessment were reduced to 77 and 63% predicted respectively and were similar to patients with sporadic LAM. During follow-up, FEV1 fell by a mean of 81 ml/year and DLCO fell by 0.309 mmol/ml/kPa/year in patients not being treated with an mTOR inhibitor. 55% required treatment with either sirolimus or Everolimus for LAM or angiomyolipoma respectively. For those treated with an mTOR inhibitor, mean FEV1 fell by 3 ml/year and DLCO increased by 0.032 mmol/ml/kPa/year and was similar to sporadic LAM. Risk of death due to LAM or need for lung transplant in patients with TSC-LAM was 0.67%/year. Conclusions Despite screening recommendations, LAM is often diagnosed in TSC after symptoms develop which may delay treatment. Complications including pneumothorax and loss of lung function are significant and similar to sporadic LAM. Work is needed to implement the recommended CT screening for LAM and improve respiratory care for TSC-LAM.